Analisis Analisis Kinerja Bank BTPN Syariah Periode 2021 – 2023 Menggunakan Metode Indeks Maqashid Syariah - Akbar Budi Sampurno; Moch Khoirul Anwar; Maryam Bte Badrul Munir (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The aim of this research is to determine the performance of BTPN Syariah bank from 2021 to 2023 using the maqashid sharia index method. The instrument for assessing the performance of sharia banks is the maqashid sharia index which measures the success of a business based on the benefits provided to the wider community. This research uses a quantitative methodology with a descriptive approach, utilizing data sources originating from the annual financial reports of BTPN Syariah bank. Research findings show that the value of the maqashid sharia index on the performance of BTPN Syariah bank has fluctuated. This shows that the performance of BTPN Syariah bank in 2021–2023 is not as good as expected in fulfilling maqashid sharia objectives. The decline in the maqashid sharia index ratio value is currently the cause of the performance of BTPN Syariah bank. Additionally, certain ratios, such as reasonable profits and personal income, cannot be calculated. This is because BTPN Syariah bank does not manage zakat funds and does not apply the PER ratio in the financial audit system in its annual financial reports.